Scrutinize of healthy school canteen policy in Iran's primary schools: a mixed method study - Mina Babashahi; Nasrin Omidvar; Hassan Joulaei; Azizollaah Zargaraan; Farid Zayeri; Elnaz Veisi; Azam Doustmohammadian; Roya Kelishadi (BMC, 2021)
Abstract Background Schools provide an opportunity for developing strategies to create healthy food environments for children. The present study aimed to analyze the Healthy School Canteen (HSC) policy and identify challenges of its implementation to improve the school food environment in Iran. Methods This mixed method study included two qualitative and quantitative phases. In the qualitative phase, triangulation approach was applied by using semi-structured interviews with key informants, documents review and direct observation. Data content analysis was conducted through policy analysis triangle framework. In the quantitative phase, food items available in 64 canteens of primary schools of Tehran province were gathered. The food's nutrient data were evaluated using their nutrition facts label. The number and proportion of foods that met the criteria based on Iran's HSC guideline and the World Health Organization nutrient profile model for the Eastern Mediterranean Region (WHO-EMR) were determined. Results The main contextual factors that affected adoption of HSC policy included health (nutritional transition, high prevalence of non-communicable diseases and unhealthy food environment in and around the schools), political (upstream supportive policies and joint memorandums about health children between the Ministry of Health and Medical Education and Ministry of Education), structural (the lack of unified stewardship, inadequate human resource capacity, poor inter-sectional cooperation), economic (school financial problems, poor fiscal supportive of food policies), and socio-cultural (mothers working outside the home, the role of children's peer group, low nutrition knowledge of school principals) factors. Assessment of the school canteens showed that a large proportion of available foods did not comply with the national guidelines (54.7 ± 2.54%) and WHO-EMR model (85.6 ± 2.34%). The main reasons identified for incomplete implementation of the policy were inadequate physical and economic infrastructure to set up standard school canteens, lack of scientific criteria for food categorization, poor monitoring, high price of healthy foods, and conflict of interest among the actors. Conclusion The majority of foods and beverages available in the school canteens did not comply with national and regional standards. Iran HSC policy needs to be improved by using an evidence-based approach and active interaction between all key actors.